KESEIMBANGAN AIR (WATER BALANCE) DI KABUPATEN SABU-RAIJUA - Ndoen, Oliver K.; Krisnayanti, Denik S.; Utomo, Sudiyo (Jurnal Teknik Sipil, 2017)
Sabu Raijua is one of districts in East Nusa Tenggara province with dry climate that have annual rainfall about 997 mm/year and including in low grade (